37 Perceptions and awareness of risk in the workplace among migrants to Australia. (11th October 2013) - Reid, A; Santos,; Hard,; Fritschi,; Lenguerrand,; Montagne, La
Abstract : Objectives: Migration has been important to the wealth and development of Australia and one in four Australians are born abroad. Our analysis of the national Multi-Purpose Household Survey showed generally higher risks in specific industrial settings but not among migrant workers. Anecdotal evidence, however, suggest that migrant workers are exposed to more workplace hazards. In qualitative interviews we explored perceptions of health and safety and experiences in home countries and in Australia. Methods: 92 purposively sampled migrant workers took part in individual interviews (n = 15) or 8 focus groups (n = 77) from 22 countries (20 from low to middle income countries (LMICs)). Migrants were sampled via migrant organisations, trade unions or via advertisements in the local press. Interviews were digitally recorded, anonymised, and transcribed verbatim. NVivo 10 was used to organise and explore coded transcripts. A concurrent thematic analysis was conducted. Themes around each category were verified and confirmed by constant comparison and searching across all interviews for similar themes and categories for analysis. Results: The key themes that emerged included poor understanding of occupational health and safety, particularly among those from LMICs and even among those with a relatively higher education level; general perception that Australia was a safe place to work in although there were reports of risky practices (e.g. long working hours) and overt discriminatory practices such as racism or bullying in workplaces; and a general resilience towards adversity in workplaces. Social support networks (e.g. via churches) or the commitment to sending remittances to family in home countries played an important role in coping with such adversity. Many tried to explain the racism as humour, and incidents were rarely reported. Conclusion: These findings of a poor understanding of health and safety among migrants from LMICs, shed some light on the context which might result in under-reporting in national surveys.